Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Pada Materi Sejarah Proklamasi Indonesia - Nabilla Nur Fauziah; Zaskia Putri Aulia Azzahra; Tin Rustini (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This research uses a qualitative method with a descriptive approach. The focus of the research is the Jigsaw type cooperative learning model in the context of social studies learning, especially regarding the proclamation of Indonesian independence. This model offers various advantages, such as increasing critical thinking skills, student motivation, and positive social interactions. However, there are drawbacks that need to be considered, such as longer time and differences in student perceptions. This study also notes that the implementation of the Jigsaw model in social studies learning can successfully increase student activity, historical awareness, and learning achievement. In practice, teachers need to prepare sub-material carefully, choose appropriate learning media, and monitor the implementation of learning. With a good understanding of this model, learning can be more effective and enjoyable for students